2017
DOI: 10.18632/oncotarget.23479
|View full text |Cite
|
Sign up to set email alerts
|

Asymmetrically enlarged parietal foramina in a rare case of Goldenhar syndrome with a possible etiopathogenesis

Abstract: Goldenhar´s syndrome (GS) also known as oculo-auriculo-vertebral spectrum (OAVS) is a relatively rare condition. GS is of multifactorial etiology that includes environmental and/or genetic factors, in addition to teratogens that disturb the blastogenesis. A 5-year-old girl from Saudi Arabia, was a member of dizygotic twins conceived by assisted reproductive technology (ART), and born with features of GS. She had asymmetrical face, cleft lip and palate, right microphthalmia and microtia. Radiological imaging sh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 17 publications
(16 reference statements)
0
2
0
Order By: Relevance
“…The posterior interparietal region of the skull has been thought to predispose to a variety of bony variants and congenital anomalies involving the scalp, skull, meninges, and adjacent cerebral cortices. 4,[6][7][8][9][10][11][12][13] In this study, 4% of the identified PF presented an obstruction around the outer opening, which may make it difficult to identify on dry skulls, cadaver specimens, and intraoperative observation. This means that the frequency of the PF may be underestimated for a superficially hidden outer opening.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The posterior interparietal region of the skull has been thought to predispose to a variety of bony variants and congenital anomalies involving the scalp, skull, meninges, and adjacent cerebral cortices. 4,[6][7][8][9][10][11][12][13] In this study, 4% of the identified PF presented an obstruction around the outer opening, which may make it difficult to identify on dry skulls, cadaver specimens, and intraoperative observation. This means that the frequency of the PF may be underestimated for a superficially hidden outer opening.…”
Section: Discussionmentioning
confidence: 99%
“…The region has been known to predispose to a variety of bony variants and congenital anomalies involving the scalp, skull, meninges, and adjacent cerebral cortices. 4,[6][7][8][9][10][11][12][13] Consequently, extensive studies have been conducted on the PFs, cranial sutures associated with the posterior interparietal region, and patterns of developmental ossifications in the region. 12,[14][15][16][17] However, to the best of our knowledge, no study has explored the bony canals of the posterior interparietal region in detail.…”
mentioning
confidence: 99%